Local anaesthesia vs. general anaesthesia for percutaneous microwave ablation in hepatocellular carcinoma: efficacy, safety, and cost analysis - Zhan, Jing-Ying; Zhao, Dan; Tang, Zhen-Lei; Leng, Hao-Qun (Frontiers in Oncology, 2023)
Purpose: To compare the efficacy, safety, and cost of local anaesthesia and general anaesthesia modalities for percutaneous microwave ablation as a curative treatment for hepatocellular carcinoma patients. Methods: This comparative, retrospective study analysed 175 patients who were treated for hepatocellular carcinoma (HCC) from July 2015 to September 2020. Conventional transcatheter arterial chemoembolization (cTACE) combined with sequential percutaneous microwave ablation (MWA) was performed on every lesion in every patient. Patients were divided into two cohorts according to the anaesthesia modality applied during MWA. To investigate the differences in efficacy between the two groups, overall survival (OS) and local recurrence-free survival (LRFS) were estimated by the Kaplan‒Meier method and compared by the log-rank test. Cost and safety between the two groups were also compared accordingly. Results: There were 105 patients with 128 HCC lesions in the local anaesthesia (LA) group and 70 patients with 107 lesions in the general anaesthesia (GA) group. There were no significant differences in OS (P = 0.798) or LRFS (P = 0.406) between the two groups. Fifty-two pairs of patients were matched with 77 lesions in the GA group and 67 lesions in the LA group after PSM. There was no significant difference in OS (P = 0.522) or LRFS (P = 0.410) between the two groups. Compared to the LA group, the GA group had longer operations, consumed more medical resources, had a heavier financial burden, and experienced more anaesthesia adverse events. There was no significant difference in the incidence of post-ablation pain (p=0.487), fever (P=0.678), nausea or vomiting (P=0.808), mild liver dysfunction (P=0.753), haemolytic uraemic syndrome (P=0.595), pleural effusion (P=0.622), liver abscess (0.544), asymptomatic perihepatic fluid (0.703) or subcapsular liver hemorrhage (P=0.666) between the two groups. Conclusion: Due to the higher cost and adverse events of general anaesthesia, local anaesthesia may be more suitable for ablation procedures for HCC patients within the Milan criteria.